A Literature Review: Digital Marketing Trends in Indonesia During the COVID-19 Pandemic - Nabila Astari (CHANNEL: Jurnal Komunikasi, 2021)
This study is about the current trend and upcoming future trends in digital marketing. They use secondary data, a literature review based on current literature, and studies about what is currently happening in the business world. Other sources are used in this study, such as articles, research, reports, news, website, and many more. During this digitization era, especially during the COVID-19 pandemic, consumers look for information and try to find the best option using the internet. It made some shifts in the market from conventional marketing to digital marketing. Now brands are using SEO, SEM, influencer marketing, and other digital marketing approaches. In this study, we acknowledge that brands receive benefits from digital marketing. All brands that prove this are racing to connect with consumers using social media and digital channels to increase consumer knowledge about the brand and create brand loyalty. This study will focus on digital marketing approaches that this study suggests for companies during the pandemic.